Close Margins in Oral Cancers: Implication of Close Margin Status in Recurrence and Survival of pT1N0 and pT2N0 Oral Cancers. (11th November 2014) - Gokavarapu, Sandhya; Chander, Ravi; Parvataneni, Nagendra; Puthamakula, Sreenivasa
Abstract : Introduction. Among all prognostic factors, "margin status" is the only factor under clinician's control. Current guidelines describe histopathologic margin of >5 mm as "clear margin" and 1–5 mm as "close margin." Ambiguous description of positive margin in the published data resulted in comparison of microscopically "involved margin" and "close margin" together with "clear margin" in many publications. Authors attempted to compare the outcome of close and clear margins of stage I and stage II squamous cell carcinoma of oral cavity to investigate the efficacy of description of margin status. Patients and Methods. Historical cohorts of patients treated between January 2010 and December 2011 at tertiary cancer hospital were investigated and filtered for stage I and stage II primary squamous cell carcinomas of oral cavity. Patients with margin status of tumor at margin or within 1mm from cut margin were excluded and analyzed in multivariate logistic regression model for locoregional recurrences and Cox regression for overall survival. Results. A total of 104 patients fulfilled the abovementioned criteria, of whom 36 were "clear margin" and 68 were "close margin" with median period of follow-up of 39 months. There was no significant difference in locoregional recurrence ( P value: 0.0.810) and survival ( P value: 0.0.851) among "close margin" and "clear margin" patients.